2016
DOI: 10.1007/s10971-016-4120-2
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel preparation of NiO/ZrO2(x)–MgO(100−x) nanocatalyst used in CO2/O2 oxidative dehydrogenation of ethane to ethylene: influence of Mg/Zr ratio on catalytic performance

Abstract: A series of NiO/MgO-ZrO 2 mixed oxide catalysts were prepared using the sol-gel method in which the content of MgO and ZrO 2 was varied and the NiO amount was maintained around 5 wt%. The synthesized samples were characterized by XRD, FESEM, PSD, TEM, EDX dot-mapping, FTIR and the BET techniques and tested for the dehydrogenation of ethane in the presence of CO 2 with limited amount of O 2 . Irrespective of the various Mg/Zr ratios, the uniform dispersion of NiO as a common feature of all synthesized samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The textural modification of nano-size adsorbents has been broadly investigated to hamper the agglomeration of nanoparticles [29][30][31][32][33][34][35]. Extensive studies have indicated the higher enhancement in the CO2 adsorption capacity of modified CaO by using ZrO2 as the promoter compared to other metal oxides [36].…”
Section: Introductionmentioning
confidence: 99%
“…The textural modification of nano-size adsorbents has been broadly investigated to hamper the agglomeration of nanoparticles [29][30][31][32][33][34][35]. Extensive studies have indicated the higher enhancement in the CO2 adsorption capacity of modified CaO by using ZrO2 as the promoter compared to other metal oxides [36].…”
Section: Introductionmentioning
confidence: 99%
“…The challenge faced by scholars is predominantly the improvement of catalytic activity and life cycle, which is strongly determined by the dispersion of metal species and coke deposition during the reaction. Different types of supports have been investigated, including those of acidic nature (Al 2 O 3 , [6] ZSM‐5, [5c,7] ZrO 2 , [8] SAPO‐34 [9] ), the neutral mesoporous SiO 2 materials, such as Silicalite‐1, [10] MCM‐41, [11] SBA‐15, [12] TUD‐1, [5b] SiO 2 [5a,13] etc ., and the mixed metal oxides of ZrO 2 ‐CeO 2 , [6a] ZrO 2 ‐MgO [14] . In revealing the significance of the acid property, appropriate acid strength ensured the activation of C−H bonds to form alkeneand prevented them from cleaving.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, various methods, such as precipitation ( Arshad et al, 2019 ; Rahdar et al, 2019 ), sol-gel ( Delir Kheyrollahi Nezhad et al, 2016 ) and high-temperature pyrolysis ( Chen et al, 2020 ), have been developed to synthesize supported nanocatalysts. These methods were developed mainly in a batch reactor, which may lead to polydispersity of nanoparticles and batch-to-batch irreproducibility ( Marre and Jensen, 2010 ).…”
Section: Introductionmentioning
confidence: 99%